Vertical product differentiation when quality is unobservable to buyers - Gerhard O. Orosel; Klaus G. Zauner (Center for Economic Studies and ifo Institute (CESifo), 2004)
We analyze vertical product differentiation in a model where a good's quality is unobservable to buyers before purchase, a continuum of quality levels is technologically feasible, and minimum quality is supplied under competitive conditions. After purchase the true quality of the good is revealed with positive probability. To provide firms with incentives to actually deliver promised quality, prices must exceed marginal cost. We derive sufficient conditions for these incentive constraints to determine equilibrium prices, and show that under certain conditions only one or both of the extreme levels of quality, minimum and maximum quality, are available in the market.
Keywords: L15; L11; D82; 330; experience goods; product differentiation; product quality; asymmetric information; Produktdifferenzierung; Produktqualität; Gleichgewicht; Asymmetrische Information; Ökonomischer Anreiz; Informationsverhalten; Produktinformation; Theorie; Erfahrungsgüter